2018
DOI: 10.1186/s12884-018-1772-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of immediate antepartum ultrasound estimated fetal weight and its impact on mode of delivery and outcome - a cohort analysis

Abstract: BackgroundThe aim of the study was to investigate the accuracy of ultrasound-derived estimated fetal weight (EFW) and to determine its impact on management and outcome of delivery.MethodsIn this single-center cohort analysis, women with a singleton term pregnancy in the beginning stages of labor were included. Women with immediately antepartum EFW (N = 492) were compared to women without ultrasound (N = 515).ResultsEFW was correct (deviation from birth weight ≤ 10%) in 72.2% (355/492) of patients with fetal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…The majority (80.1%) of our EFW calculations were accurate to within ±10% of LBW, similar to rates reported from the United Kingdom, Nigeria and Germany (72%-78%). 16,21,23 This is also consistent with a postpartum study by Kehl et al 22 who concluded EFW formulae should predict 80% of cases within a discrepancy level of ±10%. A recent review of 2296 pregnancies scanned within three days of delivery at regional English hospitals, indicated similar rates of accuracy for preterm (69.6%) and term deliveries (72.8%).…”
Section: 1]supporting
confidence: 87%
See 2 more Smart Citations
“…The majority (80.1%) of our EFW calculations were accurate to within ±10% of LBW, similar to rates reported from the United Kingdom, Nigeria and Germany (72%-78%). 16,21,23 This is also consistent with a postpartum study by Kehl et al 22 who concluded EFW formulae should predict 80% of cases within a discrepancy level of ±10%. A recent review of 2296 pregnancies scanned within three days of delivery at regional English hospitals, indicated similar rates of accuracy for preterm (69.6%) and term deliveries (72.8%).…”
Section: 1]supporting
confidence: 87%
“…While Barel et al 18 reported that fetal sex, presentation and AFI did have a significant effect on EFW (reported as mean PE), they suggested that their contribution was small and of uncertain clinical consequence. Overestimation of smaller fetuses has been reported 23,28,29 and although there was no significant association between birthweight category and accuracy in our sample, there was a tendency to overestimate across all categories, but more so in the low (mean AE 8.1%) and macrosomic birthweight categories (mean AE 7.1%) compared to the normal birthweight category (mean AE 6.1%). This overestimation is consistent with Campbell Westerway 19 who compared six commonly used ultrasound EFW formulae against the 1999 Australian birthweights and demonstrated that after 37 weeks GA, EFW significantly overestimated the birthweight and the highest random error occurred in macrosomic fetuses.…”
Section: Factors Contributing To Estimated Fetal Weight Inaccuraciescontrasting
confidence: 65%
See 1 more Smart Citation
“…Increasing newborn head circumference (HC) is associated with adverse events such as obstetric anal sphincter injuries (OASIS) and emergency caesarean sections (CSs) 1‐7 . While sonographic HC correlates to newborn HC, it has a tendency to overestimate 8 . Limited studies examining sonographic HC have found an association with caesarean delivery; however, there is conflicting evidence whether sonographic HC is associated with OASIS 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In addition, given that fetal ultrasound biometry has a margin of error of 10% to 40%, depending on the clinical situation, fetal biometrics are not su ciently accurate to justify relying on their use alone. 27 Despite the absence of clinical practice guidelines provided by professional societies due to insu cient evidence regarding the effectiveness of pelvimetry, approximately 10% of pregnant women in France undergo the procedure. 28 Criteria for the reliable assessment of CPD-related traumatic delivery risks do not exist, and many ECSs and IVDs currently cannot be predicted.…”
Section: Introductionmentioning
confidence: 99%